Exploring User Feedback in the Development of the iPosyandu Mobile Application: A Phenomenological Study through Focus Group Discussion - Sakina Abdullah; Salmah Suciaty; Fedri Ruluwedrata Rinawan (Journal of Innovative and Creativity, 2025)
This study aimed to explore user feedback in the development of the iPosyandu mobile application through a phenomenological approach using Focus Group Discussion (FGD). The research focused on understanding users’ experiences regarding usability aspects such as ease of use, appearance and satisfaction, and usefulness. A total of 12 participants were selected based on their MAUQ (Mobile Health App Usability Questionnaire) scores and divided into two groups according to network conditions: good signal and poor signal areas. Data were collected through FGDs and analyzed thematically. Three main themes emerged: Ease of Use, Appearance and Satisfaction, and Usefulness. Participants generally found the application useful and visually appealing, although some issues were reported, including slow response time in low connectivity areas and limited offline functionality. Based on user input, recommendations for improvement include adding an offline mode, implementing appointment reminder notifications, and enhancing interface clarity. This study contributes to the understanding of user-centered design principles in m-Health applications, particularly in regions with varying technological accessibility. The findings provide practical insights for developers and stakeholders to enhance the iPosyandu application to better meet user needs and local context challenges.